Dietary antioxidant vitamin intake and lung function in the general population - Britton, J R; Pavord, I D; Richards, K A; Knox, A J; Wisniewski, A F; Lewis, S A; Tattersfield, A E; Weiss, S T (American journal of respiratory and critical care medicine, 1995)
We have investigated the relation between lung function and dietary intake of the antioxidant vitamins C and E in the general population in a cross-sectional survey of a random sample of adults from the electoral register of an administrative area of Nottingham. In 2,633 subjects 18 to 70 yr of age, we measured FEV1 and FVC, allergen skin sensitivity to grass pollen, cat fur, and Dermatophagoides pteronyssinus, pack-years smoking exposure by personal recall, and usual dietary intake of vitamins C and E by semiquantitative food frequency questionnaire. After adjustment for the effects of age, sex, height, mean allergen skin wheal diameter, and pack-years smoking history, both FEV1 and FVC were significantly and independently related to mean daily intake of vitamin C, such that a standard deviation (40 mg/d) higher vitamin C intake was associated with a 25.0 (95% CI, 5.2 to 44.8; p = 0.01) ml higher FEV1 and a 23.3 (0.94 to 45.7, p = 0.04) ml higher FVC. There was also an association between vitamin E intake and lung function, such that a standard deviation (2.2 mg) higher intake of vitamin E was associated with a 20.1 (1.3 to 40.4, p = 0.04) ml higher FEV1 and a 23.1 (1.0 to 45, p = 0.04) ml higher FVC. However, vitamin C and vitamin E intakes were significantly correlated (r = 0.29, p < 0.001), and after allowing for the effects of vitamin C there was no additional independent effect of vitamin E on either FEV1 or FVC.